Collective and individual practices in popular music: Differences between semi-professionals and professionals in Austria and Germany - Schmidt, Simon; Gruber, Hans (SAGE PUBLICATIONS LTD, 2025)
Collective and individual practices are essential for popular music bands and their members when preparing for public performances. This study addresses the interplay of collective and individual practices in a sample of 82 members of semi-professional and professional popular music bands in Austria and Germany. Utilizing a structured questionnaire, practices were assessed within collective and individual practice contexts, and attributes and experiences pertinent to the current band and individual members were examined in terms of their reciprocal interplay, differences between semi-professionals and professionals, and relationships with the experience variables of groups and individuals. The results showed that collective and individual deliberate practices and the use of practice strategies were related in both practice contexts. Members of professional popular music bands invested significantly less time in collective practice for fun and significantly more time in individual deliberate practice. The results provide deeper insights into the interplay of collective and individual practices in music bands, the differences between semi-professional and professional practice designs, and the relevance of practice and professional experience for accomplishing professional music performance in general.